1997
DOI: 10.1086/516065
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Drug Resistance inMycobacterium tuberculosisIsolates Recovered from Compliant Patients with Human Immunodeficiency Virus–Associated Tuberculosis

Abstract: We describe five compliant patients with human immunodeficiency virus (HIV)-associated tuberculosis (TB) that relapsed, with acquisition of resistance by the original Mycobacterium tuberculosis strains. Both the first and second isolates from each patient had the same IS (insertion sequence) 6110-based DNA fingerprint patterns. Three of the five patients developed TB that was resistant to rifampin alone; no mutation in the region of the rpoB gene was detected by a line probe assay in two of the isolates from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 9 publications
0
23
0
3
Order By: Relevance
“…Alguns estudos têm sugerido que a infecção pelo HIV parece favorecer a resistência secundária 27,28 . Várias hipóteses, como falhas no tratamento, reinfecção exógena 29 , interação medicamentosa com drogas para tratamento de AIDS 30 e má-absorção às drogas antituberculose, têm sido associados à resistência de M. tuber- culosis durante ou logo após o tratamento em pacientes HIV+ 31 .…”
Section: Análise Estatísticaunclassified
“…Alguns estudos têm sugerido que a infecção pelo HIV parece favorecer a resistência secundária 27,28 . Várias hipóteses, como falhas no tratamento, reinfecção exógena 29 , interação medicamentosa com drogas para tratamento de AIDS 30 e má-absorção às drogas antituberculose, têm sido associados à resistência de M. tuber- culosis durante ou logo após o tratamento em pacientes HIV+ 31 .…”
Section: Análise Estatísticaunclassified
“…However, a two-month waiting period before the first indications of treatment efficacy is very long and has implications for individual patients, control programs and clinical trials of new drugs. Moreover, the bacteria have time to adapt and develop drug tolerance 6 and resistance 7,8 during ineffective therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, also conducted in Rio de Janeiro, found no significant association between TB/HIV co-infection and resistance 15 . However, this is not the trend described in the international literature 16,17 , and according to the WHO, a large proportion of missing data on MDR-TB makes it impossible to conclude whether there is an overall association between MDR-TB and the HIV epidemic 18 . This possibility of an association must ACKNOWLEDGMENTS still be subject to further analysis in the municipality of Pelotas, since 50% of patients with HIV had a history of prior exposure to anti-TB drugs, and the TB/HIV co-infection rate found in this study (14%) corresponds to a WHO estimate for Brazil of 5% to 19% co-infection in 2009 19 .…”
Section: Discussionmentioning
confidence: 90%